Proton therapy for advanced juvenile nasopharyngeal angiofibroma - Hoeltgen, Line; Tessonnier, Thomas; Meixner, Eva; Hoegen-Saßmannshausen, Philipp; Kim, Ji-Young; Deng, Maximilian; Seidensaal, Katharina; Held, Thomas; Herfarth, Klaus; Debus, Jürgen; Harrabi, Semi B. (Cancers, 2023)
Purpose: To provide the first report on proton radiotherapy (PRT) in the management of advanced nasopharyngeal angiofibroma (JNA) and evaluate potential benefits compared to conformal photon therapy (XRT). Methods: We retrospectively reviewed 10 consecutive patients undergoing PRT for advanced JNA in a definitive or postoperative setting with a relative biological effectiveness weighted dose of 45 Gy in 25 fractions between 2012 and 2022 at the Heidelberg Ion Beam Therapy Center. Furthermore, dosimetric comparisons and risk estimations for short- and long-term radiation-induced complications between PRT plans and helical XRT plans were conducted. Results: PRT was well tolerated, with only low-grade acute toxicities (CTCAE I-II) being reported. The local control rate was 100% after a median follow-up of 27.0 (interquartile range 13.3-58.0) months. PRT resulted in considerable tumor shrinkage, leading to complete remission in five patients and bearing the potential to provide partial or complete symptom relief. Favorable dosimetric outcomes in critical brain substructures by the use of PRT translated into reduced estimated risks for neurocognitive impairment and radiation-induced CNS malignancies compared to XRT. Conclusions: PRT is an effective treatment option for advanced JNA with minimal acute morbidity and the potential for reduced radiation-induced long-term complications.